2005
DOI: 10.2741/1631
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-2 receptor alpha in cancer

Abstract: Interleukin-2 (IL-2) is the major growth factor for activated T-lymphocytes and stimulates clonal expansion and maturation of these lymphocytes. IL-2 binds to its receptor complex, IL-2Ralpha, beta, and gamma chains, and exerts its effect via second messengers, mainly tyrosine kinases, which ultimately stimulate gene expression. The heterotrimerization of the receptor chains leads to high affinity binding for IL-2. The functional importance of IL-2Ralpha in hematopoietic cell systems is well known. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 111 publications
(159 reference statements)
1
34
0
1
Order By: Relevance
“…The data concerning the prevalence of grade IV prostatitis in patients with prostate cancer and BPH have been published previously [25]. High expression of IL-2R in tumour tissue is obviously associated with a poorer prognosis of the disease for the patient [13]. Patients with B-cell lymphoma and high sIL-2R levels in serum had a significantly poorer prognosis [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data concerning the prevalence of grade IV prostatitis in patients with prostate cancer and BPH have been published previously [25]. High expression of IL-2R in tumour tissue is obviously associated with a poorer prognosis of the disease for the patient [13]. Patients with B-cell lymphoma and high sIL-2R levels in serum had a significantly poorer prognosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…These initiate the production of interleukin, interferon and tumour necrosis factor-, and stimulate the proliferation of cytotoxic cells and lymphokine-activated killer cells, as well as the cytotoxicity of macrophages. IL-2 is referred to as a T-cell growth factor [12][13][14][15]. The regulatory T lymphocytes CD8 + and CD25 + , activated by IL-2, are found in prostate cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific basis for this is that IL2Rα is not expressed by resting cells other than Tregs and CD56 hi CD16 lo NK cells but is constitutively expressed by an array of malignant cells of various T- and B-cell leukemias as well as T cells involved in select autoimmune disorders and those that participate in organ allograft rejection (56, 59). One form of IL2 receptor-directed therapy involves the use of unarmed antibodies specific for IL2Rα including basiliximab (Simulect: Novartis AG) and daclizumab (also known as anti-Tac, Zenapax), the first humanized antibody that was approved by the FDA (56, 58, 60, 61).…”
Section: Introductionmentioning
confidence: 99%
“…IL-2 induces cell growth and differentiation with augmentation of cellular activities, and it may directly affect its target cells, or indirectly induce the expression of endogenous cytokines, such as INF-g [24]. Augmented concentrations of IL-2 and IFN-g in serum and other body fluids occur in diseases of neoplastic, infective, or autoimmune nature [25,26], but to our knowledge it has not been investigated in relationship to diabetic retinopathy. Earlier studies have only reported increased levels of the soluble receptors for IL-2 in serum [27,28] and in epiretinal membranes [10] from eyes of patients with proliferative diabetic retinopathy; however, neither IL-2 nor IFN-g increases in the retinal tissue during experimental diabetic retinopathy have been reported so far.…”
Section: Discussionmentioning
confidence: 95%